Correlation between serum ferritin levels and follicle-stimulating hormone (FSH) in patients with beta-thalassemia major at Universitas Airlangga Hospital - Laila Faiqotul Husna; Pradana Zaky Romadhon; Yetti Hernaningsih; Erika Marfiani; Kartika Prahasanti (Universitas Muhammadiyah Surabaya, 2026)
Patients with beta-thalassemia major require repeated blood transfusions. Repeated blood transfusions and increased gastrointestinal iron intake can lead to iron overload in various organs, including the pituitary gland. Iron accumulation in the pituitary gland can damage gonadotroph cells and interfere with follicle-stimulating hormone (FSH) secretion, leading to hypogonadism. This study analyzes the correlation between serum ferritin and FSH in patients with beta-thalassemia major. A cross-sectional study was conducted, enrolling adult patients (≥18 years) with beta-thalassemia major undergoing transfusions at Airlangga University Hospital's Medical Hematology-Oncology Clinic. The analysis was performed using Spearman’s Rho correlation test. Out of 51 patients, 29 were female (56.9%) and 22 were male (43.1%), with a median age of 25 years. The mean serum ferritin level was 937.17 ± 210.61 µg/L, and the majority (64.7%) had serum ferritin levels <1000 µg/L. The median FSH level was 14.15 IU/L. 68.18% of male patients had FSH levels above the normal range, whereas 89.65% of female patients remained within the normal range. Spearman’s Rho analysis demonstrated no correlation between serum ferritin and FSH (r = 0.239; p = 0.092; 95% CI). In conclusion, this study found no statistically significant correlation between serum ferritin and FSH in patients with beta-thalassemia major.